2021
DOI: 10.3390/jcm10143073
|View full text |Cite
|
Sign up to set email alerts
|

Low and High Frequency Vibration Perception Thresholds Can Improve the Diagnosis of Diabetic Neuropathy

Abstract: Recent studies demonstrate neuropathic changes with respect to vibration sensitivity for different measurement frequencies. This study investigates the relationship between vibration perception thresholds (VPTs) at low and high frequencies at two plantar locations and diabetic peripheral neuropathy (DPN) severity in diabetes mellitus (DM) subjects with DPN. We examine differences of VPTs between participants with DM, with DPN, as well as healthy controls. The influence of anthropometric, demographic parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…In addition to pain, light touch and low-frequency vibration are also impaired in DDSP [ 13 , 14 , 15 ], suggesting involvement of Aβ fibers and sensory corpuscles (Meissner and Pacinian corpuscles, Merkel cell–neurite complexes; see [ 16 ]). Thus, the analysis of sensory corpuscles in cutaneous biopsies has been proposed as a “gold standard” method of diagnostic interest in some peripheral neuropathies and neurodegenerative diseases (see for a review [ 17 , 18 ]).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to pain, light touch and low-frequency vibration are also impaired in DDSP [ 13 , 14 , 15 ], suggesting involvement of Aβ fibers and sensory corpuscles (Meissner and Pacinian corpuscles, Merkel cell–neurite complexes; see [ 16 ]). Thus, the analysis of sensory corpuscles in cutaneous biopsies has been proposed as a “gold standard” method of diagnostic interest in some peripheral neuropathies and neurodegenerative diseases (see for a review [ 17 , 18 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Even with large overlaps between grades, finding large correlation coefficients in this study between baseline MF-V and follow-up CIPN18 scores at three months and one year after end of treatment (8–10 points) could hold the potential for CIPN risk ascertainment in conjunction with other risk factors. In regards to other clinically relevant outcomes, a recent study found a greater involvement of low-frequency (30 Hz) VPTs compared to high-frequency VPTs (200 Hz) in patients with diabetic peripheral neuropathy [ 38 ] and earlier MF-V findings in diabetic patients have demonstrated a correlation between low-frequency MF-V and clinically important outcomes such as the risk of diabetic foot ulcers and glycemic control in diabetic children [ 13 , 14 , 39 ]. However, correlation does not necessarily mean good sensitivity and specificity in clinical prediction [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another potential explanation for the absence of SEN effects lies in the relationship between the disease diabetes and VPT. Although it is generally well accepted that diabetes may lead to an impaired perception of plantar vibratory stimuli (e.g., [ 10 , 44 ]), a recent investigation showed that this is not necessarily the case [ 13 ]: it was shown that the severity of concomitant neuropathic deficits seems to play a more prominent role than diabetes alone [ 13 ]. Hence, we considered the Neuropathy Deficit Score (NDS) from experiment 1 and expected severe deficits to interfere with the effects of SEN stimulation, where disease-induced denervation [ 45 ] was already considered severe.…”
Section: Discussionmentioning
confidence: 99%
“…A self-written LabVIEW program ran a customized VPT protocol inspired by Mildren et al [ 27 ] that applies several sinusoidal vibration bursts (two seconds duration followed by a two to seven seconds pause) per trial [ 23 ], with the participants pressing a button as soon as they felt the probe vibrate. The mean of the last recognized and the last unperceived vibration stimulus was determined as VPT [ 13 ]. SEN stimulation was performed parallel to the measurement of the VPT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation